The effect of smoke teatment on the germination on four species of Mesembryanthemum: some preliminary observations - Janse van Rensburg, Sue (Department of Biological Sciences, 2020)
The effect of plant derived smoke on germination, extent of eosine dye penetration and amount of abscisic acid (ABA) in the seeds of two Karoo non-fire-prone species: Ruschia caroli and Drosanthemum speciosum, and two fynbos fire-prone species: R. macowanii and D. stokoei, of Mesembryanthemum were investigated. The seed coat characteristics of each species were also investigated. Pierce et al. (1995) found that smoke promotes seed germination in the Karoo species R. caroli (scarified) and D. speciosum, whereas smoke has no effect on the germination of R. macowanii and D. stokoei (fynboss species). Results presented in this investigation support those of Pierce et al. (1995). The extent of dye penetration in smoke treated seeds if D. speciosum was significantly greater then that in untreated seeds of this species. This was due to the breakdown of some barrier, apparently in the membrane between the endosperm and the seed coat, by smoke. Seed ABA levels were reduced by smoke treatment in all four species, however this reduction was more pronounced in the smoke responsive species. Seeds coat studies revealed that the least responsive species was the only one to be covered by a waxy cuticle. Seed dormancy was a feature of the species in which seed was improved by germination, whereas the seeds of the unresponsive species, R. macowanii and D. stokoei were non-dormant. Hence, smoke appears to act as a dormancy release cue, having no, or little effect, on the seed germination of non-dormant species. Results from this study indicate that the mechanism of smoke triggered dormancy release involves the chemical alteration of the membrane bounding the endosperm and the reduction in the ABA concentration in the species investigated.